Emerging and Traditional Technologies for Safe, Healthy and Quality Food - Nedović, Viktor; Raspor, Peter; Lević, Jovanka; Tumbas Šaponjac, Vesna; Barbosa-Cánovas, Gustavo V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Since its inception in 2002, the Central European Food Congress (CEFood) has been a biannual meeting intended for food producers and distributors as well as researchers and educators to promote research, development, innovation and education within food science and technology in the Middle European region with a tight connection to global trends. The 6th CEFood, held in Novi Sad, Serbia, May 23-26, 2012, highlighted the novel technologies and traditional foods aimed at both the European and global markets. Specifically, CEFood 2012 focused on the latest progress in fundamental and applied food science, research and development, innovative technology, food ingredients, novel trends in nutrition and health, functional and bioactive food, food engineering, food safety and quality and the food and feed market. This book will consist of contributions from various presenters at CEFood 2012, covering the major themes of this Congress. Chapters contributed by expert presenters fromthe 6th CEFood Congress of 2012 Highlights the novel technologies of food science Discusses the future of the food industry and food research.
Part I: Safe and Healthy Food -- Safe Food and Healthy Diets -- Food Supply Chains vs. Food Supply Nets -- Food Safety Aspects Concerning Traditional Foods -- Factors Affecting Elimination of Carcinogenic Compounds from Food Products -- Acrylamide Formation in Foods: Role of Composition and Processing -- Detection of Bioactive Compounds in Plants and Food Products -- Beer as an Integral Part of Healthy Diets: Current Knowledge and Perspectives -- Strategy for Screening of Antioxidant Constituents in Protein Hydrolysates -- Part II: Food Quality -- Heat-induced Casein-Whey Protein Interactions in Caprine Milk: Whether are Similar to Bovine milk? -- Whey Protein Edible Coatings: Recent Developments and Applications -- Physical and Sensory Properties of High Added Value Rice Extrudates -- Quality Standardization of Traditional Dry Fermented Sausages: Case of Petrovská Klobása -- Part III: Food Biotechnology -- Traditional and Emerging Technologies for Autochthonous Lactic Acid Bacteria Application -- Effect of Cell Immobilization on Properties of Presumptive Probiotics -- The Biocide and Antibiotic Resistance in Campylobacter Jejuni and Campylobacter Coli -- Microbial Polysaccharides: Between Oil Wells, Food and Drugs -- Part IV: Food Engineering -- Food Cold Chain Management and Optimization -- Encapsulation Technologies for Food Industry -- Innovations in Food Packaging Materials -- Food Processing using Supercritical Fluids -- Aqueous Fractionation of Dry-milled Corn Germ for Food Protein Production.
Keywords: Food science; Biotechnology; Food Science; Chemical Bioengineering